Regulatory Disharmony of NFTs and the Problematics of Smart Contract Validity: Implications for the Law of Obligations and Fiduciary Security - Anwar, Gamitra; Al-Fatih, Sholahuddin; Arief, Sofyan (JURNAL AKTA, 2025)
This study analyzes the fundamental regulatory disharmony concerning Non-Fungible Tokens (NFTs) and smart contracts within the Indonesian Civil Law system. The root of the problem is identified as a rechtsvacuüm (legal vacuum) and the "ontological silence" of the Indonesian Civil Code (KUHPerdata), which fails to provide a definitive property status (zaak) for digital assets. This failure of the lex generalis triggers a "Regulatory Trilemma," wherein the status of NFTs is fragmented among the commodity regime (Bappebti), property law (KUHPerdata), and Intellectual Property Rights (Copyright Law). This normative-juridical research finds that such disharmony creates a domino effect in two realms. First, it threatens the substantive validity of smart contracts regarding the objective requirement of "a certain subject matter" (Article 1320 of the KUHPerdata) and confronts the adage 'code is law' with the principle of "good faith" (Article 1338 of the KUHPerdata). Second, the potential of NFTs as objects of fiduciary guarantee (UUJF) becomes practically paralyzed due to fundamental obstacles in valuation, registration (centralization vs. decentralization), and execution (private keys). Through a comparative law approach utilizing the Singaporean ruling of Janesh v. Chefpierre, this study recommends the adoption of "functional reasoning" through judicial rechtsvinding and legislative reform of the KUHPerdata to fill the legal void.